The Dead Unborn, Postmortem Privacy Cases, and Abortion Rights - Allen, Anita L. (The Hastings Center report, 2024)
The privacy of the dead is an interesting area of concern for bioethicists. There is a legal doctrine that the dead can't have privacy rights, but also a body of contrary law ascribing privacy rights to the deceased and kin in relation to the deceased. As women's abortion privacy is under assault by American courts and legislatures, the implications of ascribing privacy rights to embryos and fetuses is more important than ever. Caution is called for in this domain.